(untitled) (Journal of University of Babylon for Engineering Sciences, 2019)
Architecture is based on a set of formation rules based on mutual dialogue with its temporal and spatial environment. Value systems in all their forms represent one of the most influential factors in the formation of architecture. As the Islamic approach has value systems formed by the moderation approach which is based on integration and balance between the duals while conserving the elements in its time and place. The Arabic Islamic architecture seeks to make the characteristics of the Islamic moderation values ​​ the main approach in the formulation and composition in alignment time and place. A commitment to these characteristics represents the preservation of the authenticity, gravity and balance of Arabic Islamic architecture. The general research problem emerges as being the lack of knowledge about the effect characteristics of moderation values ​​on Islamic approach, while the focus of this research is related to understand the nature of the relationship between the value as amoderation system and the composition in the Arabic Islamic architecture. As a result, the research problem was formulated as the lack of enough knowledge about the characteristics of moderation values and their impact on composition of Arabic Islamic architecture and its formulation at both intellectual and formal levels and their reflection on mosques composition. The objective of the research is to construct a comprehensive theoretical framework that tries to enhance the understanding of characteristics of moderation value system and its effect on composing of Arabic Islamic architecture and its formulation on both intellectual and formal levels. This study assumed that the variance of the characteristics of the values system leads to the variation of composition Arabic Islamic architecture. To check this hypothesis, its application was investigated in mosques a case study. It’s concluded that the temporal and spatial characteristics of the value system are the most influential factors in composing Arabic Islamic architecture, followed by other characteristics.